2005
DOI: 10.1074/jbc.m503736200
|View full text |Cite
|
Sign up to set email alerts
|

Control of ASPP2/53BP2L Protein Levels by Proteasomal Degradation Modulates p53 Apoptotic Function

Abstract: The p53 pathway is a central mediator of the apoptotic response. ASPP2/ 53BP2L (apoptosis-stimulating protein of p53 2, also known as 53BP2L) enhances apoptosis through selective stimulation of p53 transactivation of proapoptotic target genes. Although the Rb/E2F pathway regulates ASPP2/ 53BP2L transcription, the complex mechanisms controlling ASPP2/ 53BP2L levels and function remain unknown. We now report that proteasomal degradation modulates ASPP2/ 53BP2L protein levels and apoptotic function. Treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…ASPP2 knockdown, on the other hand, did not significantly increase the survival of unstressed cells (Zhu et al, 2005), which was confirmed in this study. On UV treatment of ASPP2 knockdown cells, Ddx42p showed no obvious protective effect.…”
Section: Ddx42p Counteracts Aspp2supporting
confidence: 87%
See 3 more Smart Citations
“…ASPP2 knockdown, on the other hand, did not significantly increase the survival of unstressed cells (Zhu et al, 2005), which was confirmed in this study. On UV treatment of ASPP2 knockdown cells, Ddx42p showed no obvious protective effect.…”
Section: Ddx42p Counteracts Aspp2supporting
confidence: 87%
“…In otherwise unstressed cells, ASPP2 overexpression causes little reduction in cell viability, which corresponds to former results (Zhu et al, 2005). After varying doses of UV stress, the fraction of viable cells is decreased on ASPP2 overexpression, and simultaneous overexpression of mutant Ddx42p(1-737) did not rescue cells.…”
Section: Ddx42p Counteracts Aspp2supporting
confidence: 81%
See 2 more Smart Citations
“…Treatment of cells with bortezomib, a specific inhibitor of the proteasome which is clinically active in different tumour types, increased ASPP2 protein and protein half-life but not RNA levels (Zhu et al, 2005). Treatment with anthracycline, a chemotherapy agent that can induce DNA damage and inhibit the proteasome, also increased ASPP2 protein but not RNA levels.…”
Section: Regulation Of Aspp2 Expression At the Protein Levelmentioning
confidence: 99%